Epidemiology and Risk Factors in Non-infectious Uveitis: A Systematic Review - Joltikov, Katherine A.; Lobo-Chan, Ann-Marie (Frontiers in Medicine, 2021)
Purpose: Non-infectious uveitis is a leading cause of vision loss in the developed world. The purpose of this systematic review is to investigate the epidemiology and risk factors of non-infectious uveitis over the last 50 years. Methods: A systematic literature search of Pubmed/MEDLINE database was performed in the 50-year period from January 1971 to January 2021, according to the PRISMA guidelines. Studies that assessed the epidemiology and risk factors for non-infectious uveitis were included. Results: Few epidemiologic studies focus specifically on non-infectious uveitis. In the Unites States, the estimated prevalence of non-infectious uveitis is 121/100,000. The incidence and prevalence varies considerably worldwide. Females and the working age group (20-50 years) appear to be the most affected. Smoking and vitamin D deficiency are the biggest risk factors for non-infectious uveitis, while pregnancy appears to be protective. Additional risk factors include presence of other autoimmune diseases (thyroid disease, diabetes, celiac), pre-eclampsia/eclampsia, psychological stress, and certain medications (bisphosphonates, immune checkpoint inhibitors, and female hormone therapy). Discussion: Our systematic review summarizes the incidence and prevalence of non-infectious uveitis and associated modifiable and non-modifiable risk factors.